Pengaruh Persepsi Wajib Pajak Tentang Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak dengan Kondisi Keuangan Wajib Pajak dan Preferensi Risiko Sebagai Variabel Moderating (Studi Empiris Terhadap Wajib Pajak Orang Pribadi di Kota Semarang) (Students' Journal of Accounting and Banking, 2014)
This research aims to examine the effect perception of tax service quality on taxpayer’s compliance. This research also aims to examine the moderating effect of financial condition of taxpayer’s and risk preference for the relationship between perception of tax service quality with taxpayer’s compliance. The sampling method of this research used convenience sampling with a sample of 100 respondent from individual taxpayer’s in Semarang City.The research data used are the primary data by questionnaire which have contained respondent answer’s. Is this research, data analysis, used by Moderated Regression Analysis.The result of this study indicates that the effect perceptions of tax service quality authorities of tax and risk preferences and significant positive effect, the financial condition of the taxpayer has no effect on tax compliance. Besides the two moderating variable’s that taxpayer’s financial condition and risk preferences does not affect the relationship between the taxpayer’s perception about the quality of the service tax authorities taxpayer’s compliance.Keywords: perception of tax service quality, financial condition of taxpayer’s, risk preference, and taxpayer’s compliance